ANALYSIS OF THE LAJNAH BAHTSUL MASAIL NU FATWA METHOD ON DIVORCE JOKES - Musthafa, Halum; Firdaus, Firdaus; Azwar, Zainal (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
The Lajnah Bahtsul Masail issued a fatwa regarding jokes about divorce through NU Online. In this case, someone asked whether someone who jokes about divorce has incurred thalak, and NU Online provided an answer to this question. Lajnah Bahtsul Masa'il is an NU discussion forum that explores legal issues arising from the community. Bahtsul Masail. 'Bahtsul' refers to research, discussion, and exploration. Masail, on the other hand, refers to questions, issues, problems, cases and events. Thus, linguistically, 'bahtsul masail' can be interpreted as 'discussion of a problem'. This study aims to understand the Lajnah Bahtsul Masail method of issuing a law from a problem, particularly with regard to the issue of divorce jokes. The research method employed was a literature study involving data collection through the analysis of various scientific sources, such as journals and books. The results of the study show that Bahtsul Masail uses several methods to explore a law, including the Qauli, Ilhaqi, and Manhaji methods. When answering questions about the law of divorce jokes, Bahtsul Masail uses the Manhaji method, applying the rules of Imam As-Suyuti in the book Al-Asybah Wan Nazhair, although initially the answerer refers to the book Fathul Muin